Social exclusion, infant behavior, social isolation, and maternal expectations independently predict maternal depressive symptoms. Issue 1 (29th November 2012) - Eastwood, John; Jalaludin, Bin; Kemp, Lynn; Phung, Hai; Barnett, Bryanne; Tobin, Jacinta
Abstract The objective of the study was to identify latent variables that can be used to inform theoretical models of perinatal influences on postnatal depressed mood and maternal–infant attachment. A routine survey of mothers with newborn infants was commenced in South Western Sydney in 2000. The survey included the Edinburgh Postnatal Depression Scale (EPDS) and 46 psychosocial and health‐related variables. Mothers (n = 15, 389) delivering in 2002 and 2003 were surveyed at 2–3 weeks for depressive symptoms. Nonlinear principal components analysis was undertaken to identify dimensions that might represent latent variables. Correlations between latent variables and EPDS >12 were assessed by logistic regression. A five‐dimension solution was identified, which accounted for 51% of the variance among the items studied. The five dimensions identified were maternal responsiveness, social exclusion, infant behavior, migrant social isolation, and family size. In addition, the variable maternal expectation contributed significantly to total variance and was included in the regression analysis. Regression on EPDS >12 was predictive for all variables except for maternal responsiveness, which was considered an outcome variable. The findings are consistent with the proposition that social exclusion, infant behavior, social isolation among migrant mothers, and maternal expectations are determinants of maternal mood.